Application of pediatric donors in split liver transplantation: Is there an age limit?. Issue 3 (10th November 2019) - Gao, Wei; Song, Zhuolun; Ma, Nan; Dong, Chong; Meng, Xingchu; Sun, Chao; Qin, Hong; Han, Chao; Yang, Yang; Zhang, Fubo; Zheng, Weiping; Shen, Zhongyang
Abstract : The experience of using pediatric donors in split liver transplant is exceedingly rare. We aim to investigate the outcomes of recipients receiving split pediatric grafts. Sixteen pediatric recipients receiving split liver grafts from 8 pediatric donors < 7 years were enrolled. The donor and recipient characteristics, perioperative course, postoperative complications, and graft and recipient survival rates were evaluated. The mean follow‐up time was 8.0 ± 2.3 months. The graft and recipient survival rates were 100%. The liver function remained in the normal range at the end of the follow‐up time in all recipients. No life‐threatening complications were seen in these recipients, and the only surgery‐related complication was portal vein stenosis in 1 recipient. Cytomegalovirus infection was the most common complication (62.5%). The transaminase level was significant higher in extended right lobe recipients in the early postoperative days, but the difference vanished at the end of first week; postoperative complications and graft and recipient survival rates did not differ between left and right graft recipients. Notably, the youngest split donor graft (2.7 years old) was associated with ideal recipient outcomes. Split liver transplant using well‐selected pediatric donors is a promising strategy to expand pediatric donor source in well‐matched recipients. Abstract : This study demonstrates that liver grafts from pediatric donors younger than 7 years old can safely be split and allocated to well‐selected pediatric patients.